A revolving algae biofilm based photosynthetic microbial fuel cell for simultaneous energy recovery, pollutants removal, and algae production - Zhang, Huichao; Yan, Qian; An, Zhongyi; Wen, Zhiyou (Frontiers in Microbiology, 2022)
Photosynthetic microbial fuel cell (PMFC) based on algal cathode can integrate of wastewater treatment with microalgal biomass production. However, both the traditional suspended algae and the immobilized algae cathode systems have the problems of high cost caused by Pt catalyst and ion-exchange membrane. In this work, a new equipment for membrane-free PMFC is reported based on the optimization of the most expensive MFC components: the separator and the cathode. Using a revolving algae-bacteria biofilm cathode in a photosynthetic membrane-free microbial fuel cell (RAB-MFC) can obtain pollutants removal and algal biomass production as well as electrons generation. The highest COD removal rates of the anode and cathode chambers reached 93.5±2.6% and 95.8%±0.8%, respectively. The ammonia removal efficiency in anode and cathode chambers was 91.1±1.3% and 98.0±0.6%, respectively, corresponding to an ammonia removal rate of 0.92±0.02 mg/L/h. The maximum current density and power density were 136.1 mA/m2 and 33.1 mW/m2. The average biomass production of algae biofilm was higher than 30 g/m2. The 18S rDNA sequencing analysis the eukaryotic community and revealed high operational taxonomic units (OTUs) of Chlorophyta (44.43%) was dominant phyla with low COD level, while Ciliophora (54.36%) replaced Chlorophyta as the dominant phyla when COD increased. 16S rDNA high-throughput sequencing revealed that biofilms on the cathode contained a variety of prokaryote taxa, including Proteobacteria, Bacteroidota, Firmicutes, while there was only 0.23%~0.26% photosynthesizing prokaryote found in the cathode biofilm. Collectively, this work demonstrated that RAB can be used as a bio-cathode in PMFC for pollutants removal from wastewater as well as electricity generation.